Teachers and students together in a professional learning community - Wennergren, Ann-Christine; Blossing, Ulf (Scandinavian Journal of Educational Research, 2017)
Students represent the majority of the people in a school organisation, but are rarely considered as participants in literature on professional learning communities (PLC). This article explored a PLC with the legitimate participation of students in the classroom. Data was based on interviews with 11 teachers. Community of practice theory provides 3 dimensions that were used as analytical tools: shared repertoire, mutual engagement, and joint enterprise. Shared repertoire refers to how teachers introduce and develop tools for learning; mutual engagement to how to establish relationships and atmosphere with a respect for learning; and joint enterprise to how students’ associations and experiences are used to shape content knowledge in planning for learning. We conclude that the theory of community of practice is useful to describe and understand the formation of a PLC.
Keywords: collaborative learning; community of practice; professional learning community; student participation